Sahabe dönemi hadis rivayetinde tesebbüt, iklal ve iksar - Arpaçukuru, Osman (My University, 2006)
SAHABE DÖNEMİ HADİS RİVAYETİNDE TESEBBÜT, İKLAL VE İKSAR Sahabenin hadis rivayetinde adalet sahibi oldukları ve birbirlerine asla yalan söylemedikleri, onlardan bazılarının yaptıkları açıklamalardan bilinmektedir. Bununla beraber bazen hadis rivayetinde genellikle hafıza ve kötü ezberden kaynaklanan birtakım hatalara düştükleri de olmuştur. Söz konusu hatalar diğer bazı sahabîler tarafından derhal tenkid edilmiş ve düzeltilmiştir. Bunun yanı sıra hadisin Hz. Peygamber’e ait olduğundan emin olup, söylemediği bir sözü Hz. Peygamber’e nispet etmemek ve yine hadis rivayetini keyfî bir iş olmaktan çıkarıp belirli prensipler altında yürütülmesini sağlamak için birtakım önlemler almışlar ve bunları uygulamaya özen göstermişlerdir. Sahabenin hadis rivayetinde göstermiş oldukları ve adına tesebbüt denilen bu titizlik, bildiğimiz kadarıyla bağımsız bir çalışmaya konu olmamıştır. Yine çalışmada “iklal” (hadis sayısının binden az olması) ve “iksar” (hadis sayısının bin ve daha fazla olması) kavramları bağlamında ravi sahabiler, rivayet ettikleri hadis sayılarına göre gruplandırılmış ve hadis sayıları tablolar halinde sunulmuştur. Aynı şekilde sahabilerin rivayet ettikleri hadis miktarlarının farklı olmasının sebepleri üzerinde de durulmuştur. Bu çalışma bu alanda çalışacak olan araştırmacılara faydalı olacaktır.

ON THE HADITH RELATING TETHEBBUT, IQLAL AND IKTHAR AT THE AGE OF COMPANIONS It has been known that the companions have confidence and justice (adaleth) and they don’t lie never to each of other on the hadith relating. Nevertheless they have sometimes made mistake from the situation of bad memorization and mental factors, on the hadith relating. That the mistakes have been criticized and corrected by the some other companions immediately. However they have taken some measures for the confidence that the hadith is relating to the Prophet, and to don’t connect the word that he didn’t say with the Prophet, and to state that the hadith relating is not an arbitrary work, to provide to realization of hadith relating with some rules and principles, and they have taken care about the practice of that principles. The carefulness named “tethebbuth” which the companions have shown about the hadith relating, as we know it wasn’t be a subject to any autonomous study. At the same time hadith relating of the companions, is taken up from the point of quantity in this study. On the context of words “iqlal” (Piece of hadith relation lower than one thousand) and “ikthar” (Piece of hadith relation one thousand and higher than one thousand), that the companions who relate hadith, were classified as quantity of hadith that they have related. Pieces of hadith has been presented as schedule. In addition dwelled upon the causes of differency of quantity of hadith relating. This study, will be useful for the researchers who studies on this area.
Keywords: Hadis; İslam Dini